2017
DOI: 10.1002/cssc.201700157
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Strategy for the Synthesis of Ethylene Glycol by Oxamate‐Mediated Catalytic Hydrogenation

Abstract: The present study reports an improved approach for the preparation of ethylene glycol (EG) by using carbon monoxide as C1 chemical by a two-step oxidative carbonylation and hydrogenation sequence. In the first step, oxamates are synthesized through oxidative cross double carbonylation of piperidine and ethanol by using Pd/C catalyst under phosphine ligand-free conditions and subsequently hydrogenated by Milstein's catalyst (carbonylhydrido[6-(di-t-butylphosphinomethylene)-2-(N,N-diethylaminomethyl)-1,6-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Soon after, Bhanage reported a modified two-step synthesis of ethylene glycol using oxidative carbonylation of piperidine and ethanol followed by subsequent hydrogenation of the product oxamates using the Milstein catalyst Ru13 ( Scheme 68 ). 427 The first step, oxidative carbonylation of piperidine and ethanol, was performed by an earlier established method reported by the same group. 428 Conditions for the second step, hydrogenation of oxamides, were optimized by using several ruthenium catalysts and varying the temperature, solvent, and base.…”
Section: Ethylene Glycol Production From Co and Hmentioning
confidence: 99%
“…Soon after, Bhanage reported a modified two-step synthesis of ethylene glycol using oxidative carbonylation of piperidine and ethanol followed by subsequent hydrogenation of the product oxamates using the Milstein catalyst Ru13 ( Scheme 68 ). 427 The first step, oxidative carbonylation of piperidine and ethanol, was performed by an earlier established method reported by the same group. 428 Conditions for the second step, hydrogenation of oxamides, were optimized by using several ruthenium catalysts and varying the temperature, solvent, and base.…”
Section: Ethylene Glycol Production From Co and Hmentioning
confidence: 99%
“…In the methanol cycle, the hydrogenation of hemiaminal to methanol is rather straightforward as also shown in the hydrogenation of carbamate and urea derivatives by Ru-MACHO and similar pincer complexes. 53,[124][125][126][127][128][129][130][131] Scheme 4 shows two key resting state complexes A and B. The formation of metal-formate complex A via metal-hydride transfer to CO 2 followed by rearrangement in II with a small energy barrier is thermodynamically favored due to both metaloxygen bonding and N-HÁ Á ÁO hydrogen bonding interactions.…”
Section: Metal/nh Bifunctional Molecular Catalystsmentioning
confidence: 99%
“…As oxamides can serve as important feedstocks for the production of bulk chemicals, such as oxalic acid, oxalates, and ethylene glycol, ,, the development of heterogenous catalytic systems is highly desirable for many reasons, including the ease of continuous production and reusability of the catalyst and environmental compatibility. Recently reported encouraging progress showed that a Au/hydrotalcite (HT) catalyst can catalyze the CO oxidative coupling producing oxamides at relatively high temperatures of 110–150 °C .…”
Section: Introductionmentioning
confidence: 99%